Guitar Instrumentalization, Education-Stewardship, and Musician Subject Ethics - Daniel, Daniel; Sihombing, Octa Maria (Journal of Student Research, 2023)
Underlying this research begins with a critical reflection on the subject's experience as a musician in a church located in Palangka Raya as a church clergy guitarist as well as seeing complex rhythmic stretches when encountering expression, stewardship, phonemes, worship works, ethics and self-ability. This research method uses qualitative research methods by searching data through secondary sources, namely through recent journals (the last five years) that relate to guitarists, guitars, educational stewardship based on the critical reflection of the researchers. The results of this study show that the church music guitarist embraces humility, sharing sounds/phonemes by eliminating the dominance of the guitar sound when collaborating with non-guitar instrumentalists. It then becomes a space for critical reflection when researchers retell it in the philosophical, theological and liturgical landscape of the church